Observations on the Diversity of Bird Species, and Their Role in the Bukit Soeharto Protection Forest, East Kalimantan - Jarwadi Budi Hernowo (Media Konservasi, 1989)
Bird observations in the tropical rain forest of the Bukit Soeharto Protection Forest conducted in 1986 and 1987, had identified 157 bud species. The observation was focussed the diversity of birds, behaviour, group size, habitat types, feeding and resting sites. The diversity of species was especially correlated with the forest condition such as habitat differences, forest composition andstructure.Some of the birds played important roles in the regeneration of the forest, such as in seed dispersal and pollination. Among them were hornbill (Bucerotidae), sunbirds and spiderhunter (Nectarinidae), barbets (Capitonidae), bulbuls (Pycnonotidae) and broadbill (Eurylairnidae).